Eocene seismogenic reactivation of a Jurassic ductile shear zone at Cap de Creus, Pyrenees, NE Spain. (May 2020) - Vissers, Reinoud L.M.; Ganerød, Morgan; Pennock, Gill M.; van Hinsbergen, Douwe J.J.
Abstract: The Cap de Creus peninsula in NE Spain exposes Variscan amphibolite-facies rocks, transected by greenschist-facies mylonitic shear zones accommodating displacements of up to 1 km. One of these shear zones contains pseudotachylytes with 1–4 mm thick fault veins and cm-scale high-angle injection veins and breccias. The pseudotachylyte matrix encloses mm-to μm-scale wallrock fragments and consists of ultrafine biotite and feldspar, often with a microporphyritic structure suggesting crystallization from a melt. Recent dating of the host shear zone yielded a Jurassic (170-160 Ma) age. Here we present 40 Ar/ 39 Ar dating of the pseudotachylytes yielding Early Eocene ages between 52.76 ± 1.64 Ma and 44.55 ± 0.77 Ma, indicating Alpine brittle faulting at times that Jurassic low-angle ductile shears had been tilted to their present vertical position following Alpine thrusting in the Pyrenees. The kinematics of the pseudotachylytes suggest strike-slip reactivation along the host shear zone, consistent with plate-kinematic analyses indicating coeval Iberia - Europe motion dominated by strike-slip. The dimensions of the pseudotachylyte-bearing zone and estimated brittle displacements suggest a moment magnitude of ~4.7–4.9. The average thicknesses of the fault veins indicate deformation at ≥4 km depth, an energy density of ~9.10 6  J/m 2 and a frictional resistance of ~23 MPa.